HUMAN CAPITAL AS A SOURCE OF STRATEGY FOR ACHIEVING ORGANIZATIONAL PERFORMANCE - Hasanah Hasanah; Sunarti Sunarti (LPPM STIE Muhammadiah Bandung, 2022)
Due to the fierce competition in today's global economy, many businesses are constantly looking for ways to differentiate themselves. Companies in the modern day must invest in and keep their human capital in good shape because of how dependent they are on it. If they want to succeed in today's competitive business climate, companies need to choose employees who are committed to the same strategic goals they are. To do this, businesses must invest in human capital development as a means to improve their bottom line. The research strategy used in this investigation is a combination of literature reviews and qualitative methods. Researchers in this article will look at the nature of human capital, how it is defined, and how it relates to business goals. On the other hand, he thinks HR should be driven by business goals. The study concludes that, to achieve their strategic goals, such as improved business performance, companies should allocate resources toward developing the human capital those goals demand.